Localising Global Standards in Toba, Indonesia Through a Tourist-Centric Perspective of UNESCO Guidelines - Rachmat Mulyana; I Wayan Koko Suryawan; Iva Yenis Septiariva; Sapta Suhardono; Mega Mutiara Sari; Nova Ulhasanah; Nur Novilina Arifianningsih; Wisnu Prayogo; Dwinto Martri Aji Buana (Forum Geografi)
This study examines the response to and support of the UNESCO recommendations on behalf of geo-tourism using the actual perspectives of tourists visiting the Toba region. The study employed a detailed map of Toba Geo-tourism in the Sumatra Utara Province, Indonesia, to provide a comprehensive understanding. The research was underpinned by a random sampling approach, gathering responses from a broad spectrum of tourists. The results captured an optimistic landscape, demonstrating a clear synergy between the UNESCO recommendations and the sentiments of the tourists. Not only did the guidelines resonate, but there was also a palpable feeling among tourists to either extend their stay or make a subsequent visit, provided the recommendations were implemented holistically. This study stresses the value of adopting and localising global sustainable tourism standards to suit a region such as Toba’s unique attributes and tourist expectations. By means of this research, we aim to amplify that dialogue, charting a path for Toba and similar regions to embrace a future that is both ecologically sensitive and visitor centric.